VD_FINDINFO Pron / 2013 / 279 vom 28. Oktober 2013 - VD Tribunal cantonal (2013)
TRANSACTION JUDICIAIRE, RADIATION DU RÔLE | 105 al. 1 CPC (CH), 109 al. 1 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 2 al. 1 RAJ, 65 al. 2 TFJC (2010), 67 al. 2 TFJC (2010)